Comparative Analysis of Space Efficiency in Contemporary Tall Buildings: Residential, Office, Hotel and Mixed-Use Functions - Ilgın, Hüseyin Emre; Aslantamer, Özlem Nur (International Journal of Architectural Engineering Technology, 2024)
This paper offers an in-depth comparative analysis of space efficiency in contemporary tall towers, specifically focusing on residential, office, hotel and mixed-use functions (166 cases in total). To the best of current knowledge, no study in the existing literature has focused on this critical and topical subject. The findings underscore the pivotal importance of central core planning and prismatic building forms, which emerge as crucial design elements for optimizing space efficiency across all building types. Central core planning ensures the strategic placement of essential elements like elevators and stairwells, thereby minimizing wasted space and maximizing usable floor area. Meanwhile, prismatic building forms, characterized by their straightforward geometric shapes, facilitate more efficient construction processes and space usage. Average space efficiencies of residential, office, hotel and mixed towers were 76%, 71%, 81%, and 71%, whereas core area to GFA ratio were 19%, 26%, 16% and 26%, respectively. Values fluctuated from the lowest of 55% and 4% to the highest of 94% and 38%. By exploring these dimensions, this research offers valuable insights for the architects and developers, guiding them in the creation of tall buildings that are not only architecturally impressive but also economically viable and highly efficient. This comprehensive analysis serves as a critical resource, emphasizing the need for a balanced approach that considers core planning, structural integrity, and material choice in the design and construction of tall edifices. This holistic perspective is essential for professionals aiming to achieve the highest standards of efficiency and practicality in their architectural endeavors.